Etika Sosial Pengamal Sholawat Wahidiyah - Jannah, Siti Miftakhul (Spiritualita, 2021)
In everyday life, people who practice sholawat wahidiyah have ethical values in social relations such as moral values and noble morals (akhlaqul karimah). In Surat Village, Mojo District, Kediri Regency, there are routine activities carried out by sholawat wahidiyah practitioners and general activities carried out by sholawat wahidiyah practitioners and non-sholawat wahidiyah practitioners that can influence and affect social ethics. This research aims to find out the form of activities carried out by the practitioners of Sholawat Wahidiyah, thesocial ethics contained in their teachings, and how they implement them. This research uses field research, while the approach used is a qualitative approach.The results of this study revealed: (1) Mujahadah Yaumiyah (daily mujahadah or mujahadah which is carried out at least once a day), Mujahadah Usbuiyah (mujahadah which is carried out once a week), and Mujahadah 40 days (mujahadah which is carried out every six months every month of Muharram and Rajab). Then the general activities they carried out included: the commemoration of the prophet's maulid and the commemoration of isra' mi'raj. (2) The social ethics they get, namely that other than humans are taught to constantly improve akhlaqul karimah. Human beings are also taught to be interconnected both to their fellow creatures of God and to the universe through the spiritual guidance taught by The Nauseaif Sholawat Wahidiyah. (3) And theemphasis of social ethicsis that they are quite open with others. So in addition to them drawing closer to Allah Almighty, they also try to balance each other's worldliness.